2017
DOI: 10.1371/journal.pone.0188470
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic vertebral osteomyelitis of the elderly: Characteristics and outcomes

Abstract: BackgroundThe incidence of pyogenic vertebral osteomyelitis (PVO) has increased over the past two decades. One possible cause of this increase is the aging of the population, which results in more comorbidities in high income countries.ObjectiveTo better characterize the clinical presentation and outcome of PVO in the elderly.DesignWe conducted a post-hoc analysis of a previously published trial that studied treatment duration in PVO and compared the presentation and outcomes according to age.ParticipantsOur a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 19 publications
(20 reference statements)
6
27
1
3
Order By: Relevance
“…However, there is contradictory evidence about age as a prognostic factor. The post-hoc analysis of the Duration of Treatment for Spondylodiscitis (DTS) study examining 351 patients showed higher rates of severe adverse events in the ≥ 75-year-old group (45.9% vs 23.3%, p < 0.001) regardless of the severity of neurological complications or time to treatment initiation [14]. In this study, older patients were more likely to have neoplasia and chronic inflammatory diseases.…”
Section: Discussionmentioning
confidence: 58%
“…However, there is contradictory evidence about age as a prognostic factor. The post-hoc analysis of the Duration of Treatment for Spondylodiscitis (DTS) study examining 351 patients showed higher rates of severe adverse events in the ≥ 75-year-old group (45.9% vs 23.3%, p < 0.001) regardless of the severity of neurological complications or time to treatment initiation [14]. In this study, older patients were more likely to have neoplasia and chronic inflammatory diseases.…”
Section: Discussionmentioning
confidence: 58%
“…A large cohort study by Issa et al [1] reported an early (in-hospital) mortality rate of 1.7%–2.2%. Loibl et al [8] found a slightly higher in-hospital mortality of 12.4%, and Courjon et al [11] reported 1-year mortality rates at 21% in patients aged >75 years and 3% in those aged <75 years; these data demonstrate the impact of increased age on mortality risk. Also, Courjon et al [11] linked the increased mortality risk in the elderly with a greater prevalence of neoplasia in that specific cohort.…”
Section: Discussionmentioning
confidence: 96%
“…Loibl et al [8] found a slightly higher in-hospital mortality of 12.4%, and Courjon et al [11] reported 1-year mortality rates at 21% in patients aged >75 years and 3% in those aged <75 years; these data demonstrate the impact of increased age on mortality risk. Also, Courjon et al [11] linked the increased mortality risk in the elderly with a greater prevalence of neoplasia in that specific cohort. We did not replicate this finding, but we did observe that CRF, frailty, and disease severity (indicated by number of involved vertebral levels) were associated with an increased risk of mortality, consistent with previous reports [11,12].…”
Section: Discussionmentioning
confidence: 96%
“…Among primary SEA, a further distinction can be made between SEAs that are associated with pyogenic infectious spondylodiscitis (PS) and SEAs that, at least at the time of the diagnosis, are not associated with neuroradiological signs of infection of the vertebrae and/or the corresponding disks (14). Approximately 37% of patients affected by PS will develop an epidural abscess (15), and this rate is not affected by aging (16). Primary SEAs not associated with PS account (14,17) and are usually considered as due to the hematogenous spread of circulating bacteria or fungi into the epidural space (12).…”
Section: Introductionmentioning
confidence: 99%